2006
DOI: 10.1007/s11250-006-4381-9
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the distribution, host-preference and population density of Ixodid ticks affecting domestic animals in Bangladesh

Abstract: To study the distribution, host-preference and population density of ixodid ticks in Bangladesh, an attempt was made to collect adult ticks from various host animals in three distinct topographic zones, viz. flood plains, hills and steppe 'Barind'. Five species of ixodid ticks were recorded, namely, Boophilus microplus (56.3%), Haemaphysalis bispinosa (11.3%), Rhipicephalus sanguineus (14.7%), Hyalomma anatolicum anatolicum (15.0%) and Amblyomma testudinarium (2.8%). The data showed that B. microplus occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 3 publications
8
34
0
Order By: Relevance
“…Between the two tick species recorded in this study, B. microplus is widely distributed throughout the country but the distribution of A. testudinarium is restricted to hilly areas. This distribution pattern of ticks has previously been reported by Mondal et al (1995Mondal et al ( , 1996 and Islam et al (1999Islam et al ( , 2006. Dense vegetation in the hills with high rainfall above 3000mm annually may have favored the distribution of A. testudinarium (Islam et al, 2006).…”
Section: Resultssupporting
confidence: 83%
“…Between the two tick species recorded in this study, B. microplus is widely distributed throughout the country but the distribution of A. testudinarium is restricted to hilly areas. This distribution pattern of ticks has previously been reported by Mondal et al (1995Mondal et al ( , 1996 and Islam et al (1999Islam et al ( , 2006. Dense vegetation in the hills with high rainfall above 3000mm annually may have favored the distribution of A. testudinarium (Islam et al, 2006).…”
Section: Resultssupporting
confidence: 83%
“…Vatsya et al (2008) and Kumar (1996) reported that animals were infected with ticks throughout the year with maximum infestation during rainy season, moderate during summer and least during winter season. Contradictory to our findings Islam et al (2006) found that B. microplus, Ripicephalus sanguineus, Hyalomma bispinosa infestation was higher in summer season in cattle of Bangladesh.…”
Section: Discussionsupporting
confidence: 67%
“…A recent survey carried out in Bangladesh with sub-tropical monsoon climate (Islam et al, 2006) and Tamil Nadu State in India with tropical climate and little seasonal variations (Soundararajan et al, 2014) shows that H. bispinosa parasitise more goats than any other domesticated animal and that it is widely distributed. In the present study H. bispinosa was the most common species in the Wet and Intermediate Zones of Sri Lanka.…”
Section: Journal Of the National Science Foundation Of Sri Lanka 43(3)mentioning
confidence: 99%